2009
DOI: 10.1016/j.nuclphysb.2008.08.018
|View full text |Cite
|
Sign up to set email alerts
|

β-deformation for matrix model of M-theory

Abstract: A new class of deformation of the matrix model of M-theory is considered. The deformation is analogous to the so-called β-deformation of D = 3 + 1, N = 4 super-Yang-Mills theory, which preserves the conformal symmetry. It is shown that the deformed matrix model can be considered as a matrix model of M-theory on a certain curved background in eleven-dimensional supergravity, under a scaling limit involving the deformation parameter and N (the size of the matrices). The background belongs to the so-called pp-wav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…In other setups, to argue for the genus of the surface is more involved, using an approximation to Morse theory on the surface [30], and the result is inherently more fuzzy, or explicitly requires taking a limit of large matrices [32]. One can also obtain more standard fuzzy tori as zero energy configurations in higher dimensions by studying beta deformed matrix models [31].…”
Section: B From a Sphere To A Torusmentioning
confidence: 99%
“…In other setups, to argue for the genus of the surface is more involved, using an approximation to Morse theory on the surface [30], and the result is inherently more fuzzy, or explicitly requires taking a limit of large matrices [32]. One can also obtain more standard fuzzy tori as zero energy configurations in higher dimensions by studying beta deformed matrix models [31].…”
Section: B From a Sphere To A Torusmentioning
confidence: 99%
“…In the context of Matrix theory, this deformation is considered in [21] and the stable membrane solutions of different topology are studied in the continuum limit. It will be certainly very interesting to consider BPS objects with different dimensions in the matrix models described in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…For 10 dimensional IIB supergravity, pp-waves on special holonomy manifolds are studied and it is shown that the Ramond-Ramond 5-form induces a superpotential on the light cone worldsheet Lagrangian [18], while the 3-forms are responsible for Killing vector potentials [19]. More recently, inspired by [20], supersymmetric Matrix models with so-called β-deformation are studied [21], and it is illustrated that the deformation superpotential of the discretized supermembrane action is given by inhomogeneous background fluxes which have a linear dependence on transverse coordinates. It is this discovery which motivated our research on ppwaves with a generic superpotential reported in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review can be found in [12]. In this paper we follow the conventions of [67]. Functions on the membrane world-volume at fixed time, f (σ 1 , σ 2 ), g(σ 1 , σ 2 ), .…”
Section: )mentioning
confidence: 99%
“…The possibility of interpreting the block offdiagonal components in the pp-wave matrix model as the non-Abelian degrees of freedom of membranes was suggested in[28]. In[67] it was pointed out that the non-Abelian nature of membranes may explain certain interesting properties of stable solutions (corresponding to membranes with torus topology) in a deformed version of the matrix model, where configurations of membranes characterised by different winding numbers in the continuum theory become indistinguishable in the matrix model description.…”
mentioning
confidence: 99%